Examining plasminogen activator-inhibitor-1 and C-reactive protein regulation by glucocorticoids and pro-inflammatory cytokines in liver cell lines - Dale, Lieke (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.